Susceptibility of Four Rice Types to Sitophilus oryzae Linnaeus (Coleoptera: Curculionidae) - Astuti, Ludji Pantja (AGRIVITA, Journal of Agricultural Science, 2019)
The stored rice is often damaged by storage pests. As an important storage pest, Sitophilus oryzae causes significant weight loss on stored rice. The objective of this research was to evaluate the susceptibility of four rice types on Sitophilus oryzae. The research was conducted in Plant Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya from May to September 2017. There were four rice types i.e. Brown rice (Diamond variety), Milled rice (Ciherang variety), Black rice (Watudodol variety), and Red rice (BWI-1 variety). Dobie’s Index of Susceptibility was adopted to categorize each rice type. In addition, the Analysis of Variance and Tukey HSD were used to compare the differences between four rice types at α < 0.05. Based on the Susceptibility Index, milled rice was categorized as rice resistant to S. oryzae, while black, brown, and red rice were moderate resistant. The resistance of rice varieties to S. oryzae is influenced by feed quality factors i.e. the adequacy and balance of nutrients, especially ash and fat.